Molecular analysis of precursor lesions in familial pancreatic cancer. - Tatjana Crnogorac-Jurcevic; Claude Chelala; Sayka Barry; Tomohiko Harada; Vipul Bhakta; Sam Lattimore; Stipo Jurcevic; Mary Bronner; Nicholas R Lemoine; Teresa A Brentnall (PLoS ONE)
Background With less than a 5% survival rate pancreatic adenocarcinoma (PDAC) is almost uniformly lethal. In order to make a significant impact on survival of patients with this malignancy, it is necessary to diagnose the disease early, when curative surgery is still possible. Detailed knowledge of the natural history of the disease and molecular events leading to its progression is therefore critical. Methods and findings We have analysed the precursor lesions, PanINs, from prophylactic pancreatectomy specimens of patients from four different kindreds with high risk of familial pancreatic cancer who were treated for histologically proven PanIN-2/3. Thus, the material was procured before pancreatic cancer has developed, rather than from PanINs in a tissue field that already contains cancer. Genome-wide transcriptional profiling using such unique specimens was performed. Bulk frozen sections displaying the most extensive but not microdissected PanIN-2/3 lesions were used in order to obtain the holistic view of both the precursor lesions and their microenvironment. A panel of 76 commonly dysregulated genes that underlie neoplastic progression from normal pancreas to PanINs and PDAC were identified. In addition to shared genes some differences between the PanINs of individual families as well as between the PanINs and PDACs were also seen. This was particularly pronounced in the stromal and immune responses. Conclusions Our comprehensive analysis of precursor lesions without the invasive component provides the definitive molecular proof that PanIN lesions beget cancer from a molecular standpoint. We demonstrate the need for accumulation of transcriptomic changes during the progression of PanIN to PDAC, both in the epithelium and in the surrounding stroma. An identified 76-gene signature of PDAC progression presents a rich candidate pool for the development of early diagnostic and/or surveillance markers as well as potential novel preventive/therapeutic targets for both familial and sporadic pancreatic adenocarcinoma.